Mathematics Learning Activities using Vignette Activity Sequence (VAS) and Braille Clock for Visually Impaired Students - Diva Lailatul Maghfiroh; Nia Wahyu Damayanti (Universitas Muhammadiyah Mataram, 2026)
Mathematics learning for students with visual impairments is often challenging because many concepts are visual in nature, including units of time that require an understanding of the spatial position of clock hands. This condition requires a more concrete, tactile, and structured learning approach so that concepts can be understood meaningfully. This study aims to describe how Vignette Activity Sequence (VAS) based mathematics learning with braille clock media supports the understanding of time unit concepts in students with visual impairments. This study uses a double case study qualitative approach with two subjects, one with low vision and one with full blind student, selected through purposive sampling. The intervention lasted for one month through a series of VAS sessions that integrated contextual narratives, tactile exploration, and manipulative activities using braille clocks. Data were obtained through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that VAS helped both subjects understand the relationship between the movement of the short hand and the rotation of the long hand, albeit at different rates of development. The low vision subject was quicker to recognize numbers and understand time units, while the totally blind subject showed gradual improvement in tactile orientation and number touching strategies. Both experienced increased accuracy in reading time and moving the clock hands after attending repeated sessions. These findings confirm that the integration of VAS and braille clocks provides an effective and inclusive multisensory learning experience for students with visual impairments.